Predictive value of preoperative ultrasonographic measurement of gastric morphology for the occurrence of postoperative nausea and vomiting among patients undergoing gynecological laparoscopic surgery - Qiu, Weiji; Yin, Jun; Liang, Huazheng; Shi, Qiqing; Liu, Chang; Zhang, Lina; Bai, Gang; Chen, Guozhong; Xiong, Lize (Frontiers in Oncology, 2024)
Background: Pre-operative prediction of postoperative nausea and vomiting (PONV) is primarily based on the patient's medical history. The predictive value of gastric morphological parameters observed on ultrasonography has not been comprehensively assessed.Methods: A prospective observational study was conducted to evaluate the preoperative ultrasonographic measurement of gastric morphology for predicting PONV.The gastric antrum of the participants was assessed using ultrasound before anesthesia, and the occurrence of PONV in the first 6 hours and during the 6-24 hours after surgery was reported. The main indicators included the thickness of the muscularis propria (TMP) and the cross-sectional area of the inner side of the muscularis propria (CSA-ISMP). These were recorded and analyzed. Logistic regression analysis was applied to identify factors for PONV.Results: A total of 72 patients scheduled for elective gynecological laparoscopic surgery were investigated in the study. The pre-operative CSA-ISMP of patients with PONV in the first 6 hours was significantly greater than that of those without PONV (2.765 ± 0.865 cm² vs 2.349 ± 0.881 cm², P=0.0308), with an area under the curve of 0.648 (95% CI, 0.518 to 0.778, P=0.031). Conversely, the pre-operative TMP of patients with PONV during the 6-24 hours was significantly smaller than that of those without PONV (1.530 ± 0.473 mm vs 2.038 ± 0.707 mm, P=0.0021), with an area under the curve of 0.722 (95% CI, 0.602 to 0.842, P=0.003). Logistic regression analysis confirmed that CSA-ISMP was an independent risk factor for PONV in the first 6 hours (OR=2.986, P=0.038), and TMP was an independent protective factor for PONV during the 6-24 hours after surgery (OR=0.115, P=0.006).Conclusions: Patients with a larger pre-operative CSA-ISMP or a thinner TMP are prone to develop PONV in the first 6 hours or during the 6-24 hours after surgery, respectively.http://www.chictr.org.cn(ChiCTR2100055068).